PRE-ELIMINARY STUDY OF IKAN (FISH ONLINE INVESTMENT) PROTOPY BASED ON WEB APPLICATION USING AGILE SCRUM - Sari, Wina Permana; Sidharta, Hanugra Aulia (Infotech: Journal of Technology Information, 2019)
Ministry of Health (DepKes) of the Republic of Indonesia, the main problem which is an obstacle for fishermen in a small business in the field of fisheries as a matter of capital. Capital problems that can be reported according to: difficulty in accessing, capital requirements for convoluted capital, to the public ignorance of the relevant institutions. Diverting, taking a few people who then use independent capital, or make loans through informal financial institutions. The problems encountered by the fishermen make them confused and difficult to find when they need the micro business. However, this certainly can be overcome, considering how technology has developed rapidly now. In terms of technological developments, we have now switched to the era of the industrial revolution 4.0, while information and information technology has been highly developed. Seeing the facts that exist in society, technology can be used to facilitate humans in carrying out daily activities. Therefore, in view of the facts above, the writer wants to make a fisheries investment application for investors to invest the capital they need for micro-fisheries businesses and vice versa. The purpose of this research is to create a mobile and web-based Fisheries Investment application (using bootstrap) which the writer will name "Fish" taken from a fisheries investment developed using stages appropriate to the Agile Scrum method based on knowledge within in the field of Software Engineering and is equipped with basic planning models for formation systems, such as: Business Model Canvas (BMC), Use Cases, Activity Diagrams, and Mock-Ups. The results of this study can be used to help organize the distribution of prototype development scenarios to completion with a time schedule.